Exploring the dimensions for preschool service management: Teaching with love and care / C. H. Tan - Tan, C. H. (Universiti Teknologi MARA Cawangan Sarawak, 2024)
The preschools need to be well-managed and improved continuously to serve their preschoolers better as the young kids are future leaders of nations. Excellent early childhood educational services and pupil-oriented service are instrumental in developing greater learners and thereafter individuals with the right attitudes and morality for sustainable development. Qualitative research was done to explore the underlying quality attributes of the teachers and employees for excellent preschool service management. Focus Groups technique was employed. More than ten teachers were interviewed to know the best practices and continuous service improvement. The dimensions of loving and caring preschool service include: 1. Build up a team of true passion, patience and dedicated preschool staffs, 2. Attitude of the preschool teacher, 3. Attitudes towards the children, 4. Parent and local community involvement, cooperation and collaboration, 5. Provide them a safe, clean and healthy environment, 6. Wholesome curriculum, 7.Well-balanced planning teaching and learning activities, 8. Outdoor play or free play – expose children to different outdoor environments, 9. Food safety and health, 10. Pupil’s health management, and 11. Children with special needs. Relevant suggestions are provided for further improvement.